分解因式:1、(x-2)(x+3)-(x+3)²;2、-4x的3次方y+16x²y²-16xy的3次方;3、x²(x-y)+y²(y-x);4、-0.04x²+0.01y²

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/17 22:00:57

分解因式:1、(x-2)(x+3)-(x+3)²;2、-4x的3次方y+16x²y²-16xy的3次方;3、x²(x-y)+y²(y-x);4、-0.04x²+0.01y²
分解因式:1、(x-2)(x+3)-(x+3)²;2、-4x的3次方y+16x²y²-16xy的3次方;
3、x²(x-y)+y²(y-x);4、-0.04x²+0.01y²

分解因式:1、(x-2)(x+3)-(x+3)²;2、-4x的3次方y+16x²y²-16xy的3次方;3、x²(x-y)+y²(y-x);4、-0.04x²+0.01y²
1、(x-2)(x+3)-(x+3)²
=(x+3[x-2-(x+3)²]
=(x+3)(x-2-x²-6x-9)
= (x+3)(-x²-5x -11)
= -(x+3)(x²+5x + 11)
2、-4x的3次方y+16x²y²-16xy的3次方
=-4xy(x²-4xy + 4y²)
=-4xy(x-2y)²
3、x²(x-y)+y²(y-x)
=x²(x-y)-y²(x-y)
=(x-y)(x²-y²)
=(x-y)(x-y)(x+y)
=(x-y)²(x+y)
4、-0.04x²+0.01y²
=-0.01(4x²-y²)
= -0.01(2x+y)(2x-y)